The Birth of a Notation: Myths and Histories of Digital Cinema - Terrone, Enrico (Sens public, 2020)
Does the digital turn introduce a total discontinuity in the history of cinema? André Gaudreault and Philip Marion (2015) claim that it does and provide an argument in favour of such “total discontinuity” view. In this paper, I shall reject their argument by debunking one of its premises. I shall then consider an alternative perspective, the “continuity view” proposed by philosophers such as Berys Gaut (2010) and David Davies (2011), who argue that the digital turn does not break the history of cinema. Finally, I shall find middle ground between the continuity view and the total discontinuity view, arguing that although the digital turn does not involve a total discontinuity in the way films are made by filmmakers and seen by spectators, it significantly changes the way films travel, as it were, from filmmakers to spectators.